A different challenge with Benadryl: adolescent diphenhydramine ingestions reported to National Poison Database System, 2007–2020. (3rd July 2022) - Darracq, Michael A.; Thornton, Stephen L.
Abstract: Background: The US Food and Drug Administration released a warning related to potential adverse effects related to intentional misuse or abuse ingestions of diphenhydramine in September 2020. We sought to evaluate adolescent-aged (13–19 y) diphenhydramine ingestions reported to US poison control centers to characterize these exposures, adverse effects, outcomes, and trends in outcomes and reasons for ingestion. Methods: The US National Poison Database System was queried for all exposures to diphenhydramine between January 1, 2007 and December 31, 2020. Results: 47, 644 ingestions were included for analysis. An increase in the number of ingestions, percentage of cases due to an intentional reason for ingestion and suspected suicide was observed. More serious outcomes, cardiac complications, seizures, and deaths were more common following intentional ingestions and specifically suspected suicide over misuse or abuse. Conclusions: Adolescent ingestions of diphenhydramine increased between 2007 and 2020. More serious outcomes, intentional reasons, and suspected suicide also increased over the study interval. Suspected suicide was associated with cardiac complications, seizures, coma, and death at higher rates than misuse or abuse. While misuse and abuse remain a concern, public health interventions focusing on the risk that diphenhydramine pose as an agent of suicide attempt may be of higher impact.